From local markets to global legitimacy: A materialization perspective on technological innovation system's dynamics - David Ayrapetyan; Nicolas Befort; Frans Hermans (Research Policy, 2025)
The Technological Innovation Systems (TIS) literature has made considerable strides in exploring the spatial aspect of technological innovation dynamics over the past decade. Abandoning the purely national focus on TISs, scholars have theorized TIS dynamics simultaneously along multiple geographical scales, such as regional, national, and global. Yet, the conceptual and empirical insights on the local scale of TISs have been limited. This paper elaborates a local spatial perspective on TISs and elucidates how the local scale interacts with broader scales through structural couplings. We use technological materialization to define the local scale and illustrate our perspective with a case study on a local biorefining TIS evolution in France. Using event-history analysis, we explore how the local scale evolved through functional interactions both within and across the local and broader scales. The results reveal shifting configurations of TIS functions and their interactions at various scales in different periods: while the local scale was characterized by materialization of biorefining technology and local market formation, broader scales played more versatile roles by providing resources to, forming end markets for, and establishing the legitimacy of the local scale. Policy should promote biorefinery-internal markets through technological materialization and disseminate local success stories at broader scales.
Keywords: 330; local scale; materialization; Technological Innovation System (TIS); biorefining; case study